The polymerization of acetylene on supported metal clusters: Clusters - Gilb, S.; Arenz, M.; Heiz, U. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
The polymerization of acetylene was studied by thermal programmed reaction on model catalysts consisting of size-selected Ag, Rh, and Pd atoms and Pdn (1 ≤ n ≤ 30) clusters on well-characterized MgO(111) thin films. In a single-pass heating cycle experiment, benzene, butadiene, and butane were catalyzed with different selectivities as function of cluster size: palladium and rhodium atoms selectively produce benzene, and the highest selectivity for butadiene is observed for Pd6, whereas Pd20 reveals the highest selectivity for butane. Ag atoms are inert. These results provide an atom-by-atom observation of the selectivity of small cluster catalysts.